"Sonology" of Programmable Intrathecal Pumps. Issue 7 (14th February 2014) - Saulino, Michael; Gofeld, Michael
<x xml:space="preserve">Abstract</x> Objective The study aims to demonstrate the unique sonographic features of the commercially available intrathecal drug delivery systems. Methods "Not‐for‐human‐use" pumps were obtained, placed in a tray, and covered with an ultrasound phantom gel. The anterior surface of each pump was scanned and the sonographic features were observed and recorded. Results All systems have a centrally located reservoir port (RP) and a peripherally located catheter access port (CAP) that are observable on ultrasound. The RP of the SynchroMed II system (Medtronic, Minneapolis, MN, USA) appears as an anechoic depression and a break in the bright echogenic line of the superior pump surface. The CAP appears as smaller diameter conical depression outside the circular perimeter of the pump. The RP of the MedStream system (Codman & Shurtleff, Inc., Raynham, MA, USA) has a dome‐shaped appearance. The CAP appears as a smaller dome‐shaped object that is off center but still contained within the circular perimeter of the pump. Similarly, the RP of the Prometra system (Flowonix Medical Inc, Mt. Olive, NJ, USA) is a dome‐shaped object. The CAP visually appears similar to the reservoir access port of the SynchroMed II system, namely a small depression and a break in the bright echogenic line of the pump surface, outside the perimeter of the pump. Conclusion In all programmable intrathecal pumps, the RP can be readily identified sonographically. Potentially, the dome‐shaped configuration of RP for the Prometra and MedStream systems make the access easier, when compared with SynchroMed II system. Ultrasound could potentially be utilized to localize the RP and CAP for all the systems as each of the three systems has a unique sonographic appearance